The mechanical and ballistic properties of polycarbonate - Edwards, Michael R.; Waterfall, H. (Cranfield University, 2008)
Polycarbonate is commonly used as the material of riot shields. Firings of 8.3 g steel ball bearings at velocities of 23-98 ms-1 produced damage in the form of dents. Subsequent tensile testing showed a small drop in yield strength and ductility for impact velocities greater than 58 ms-1. This drop in yield strength and ductility was more marked for specimens that had been soaked in acetone for 10 minutes after ballistic impact. Soaking in n- heptane produced no similar effect to that seen with acetone. Measurements were taken of the velocities of projectiles likely to be thrown by rioters. These showed that the measured velocities were lower than those velocities that caused macroscopic damage to polycarbonate when hit by a ball bearing. Thus susceptibility to brittle failure is likely to be associated with shields that have been hit by sharp objects and exposed to solvents after impact. Mechanical stressing of polycarbonate at the point of impact by the ball bearing had no effect on the subsequent mechanical properties. This is in contrast to the embrittlement seen in polycarbonate when internal strains are present produced on fast cooling from the melt.